Análisis estructural e institucional del sector agropecuario colombiano: propuestas de políticas públicas con base en la experiencia suramericana (2014)
This research seeks to study Colombia’s agricultural main challenges in the 21st century and suggests some possible public policy strategies to solve them -- Based on the research made by the economist Prabhu L. Pingali, the authors study Colombia’s agricultural main issues on demand, public goods provision, R&D, land usage and distribution, and the effectiveness of institutions -- Then they proceed to study the agricultural sectors of other South American countries, seeking to suggest some possible public policy solutions that were applied abroad and could work in Colombia